Revisitando as políticas de saúde mental no Brasil - LEITE, Larissa Pinheiro do Rosário Oliveira (2019)
The present study aims to reflect on the principles of psychiatric reform as an opportunity for comprehensive care of the subject. Took place through a literature search in electronic databases Medline and Lilacs (2001 to 2011), with the following keywords: mental health policy, psychiatric reform and deinstitutionalization. This is the history of psychiatry in Brazil and Pará by addressing the events that changed the service to people with mental disorders, highlighting the process of psychiatric reform, which is a major focus with the deinstitutionalization of mental hospitals and consequent deconstruction of paradigms that support it. The progressive replacement of asylum practices by other therapeutic models required and still requires efforts of society as a whole, which rely on mental health policies, to ensure that the citizenship of the patient, their rights and attending to their uniqueness. This issue has been the subject of discussion not only among health professionals, but also throughout society. In Pará, the process of change in mental health care occurs with some delay compared to other states, but gives the patient a more human model using substitute care. The mental health care still has long way to go, we know the difficulties that exist in network operation, can not be greater than the will to fight so that we can increasingly improve the quality of care to these people, validating the efforts other generations and for the Psychiatric Reform is not exhausted by passing laws, understanding that each one of them is the beginning of another long journey to go.